On the boundary of (un)decidability: decidable model-checking for a fragment of resource agent logic - Alechina, Natasha; Bulling, Nils; Logan, Brian; Nguyen, Hoang Nga (2015)
The model-checking problem for Resource Agent Logic is known to be undecidable. We review existing (un)decidability results and identify a significant fragment of the logic for which model checking is decidable. We discuss aspects which makes model checking decidable and prove undecidability of two open fragments over a class of models in which agents always have a choice of doing nothing.